Agrodiesel production in Minas Gerais state semi-arid: controversies and questions - Laschefski, Klemens (2013)
The present article is a product of researches on the production process of agrofuels in Brazil and Northern Minas Gerais State, the subsidized public policies, as well as the problematic insertion of the familiar agriculture. Then, we aim at discussing the agrodiesel production in the Brazilian semi-arid, focusing on the Minas Gerais State region, approaching the characteristics of the process. For this purpose, we have made use of information acquired by the technique of the direct observation, interviews, besides statistic date available in public database. It has been considered that the agrodiesel production has been structured in the semi-arid region of the country, potentiating the soybean agro-industrial chain, as well as restructuring, in Northern Minas Gerais State, the cultivation of castor bean and the reinsertion of the familiar agriculture in the ricin chemical chain, bringing up controversies and questions among the public policy premises on the production and usage of the agrodiesel and the familiar agriculture insertion.